Laser modification of ferrite-garnet films - Budzuliak, I.M.; Yablon, L.S.; Ilnytskyi, R.V.; Budzuliak, I.I.; Ilnytskyi, N.R.; Kryvulych, R.I.; Hlubitskyi, A. I. (Physics and Chemistry of Solid State, 2025)
High-power laser irradiation influence on the magnetic and structural parameters of ferrite-garnet films was investigated. It was shown that regardless of the laser irradiation method a decrease in the maximum deformation value and its gradient from the surface side occurs (caused by the movement of defects to the film surface). That is, during laser irradiation, its thermal effect is the determining factor for the relaxation and movement of defects, when a certain temperature gradient is formed as a result. Laser irradiation of ion-implanted FGF leads to electromagnetic waves’ transmission coefficient increase by almost 20% in a wide spectral range (3500-400 cm-1) that indicates reduced concentration of absorption centres. Crystal structure partial restoration as laser irradiation result leads to а- and d- sublattices superexchange interaction ordering that exhibited an increase of about 5-20% in the effective magnetic fields at the Fe57 nuclei for all used implantation doses.